Research progress on moxibustion in the treatment of urinary incontinence in the elderly (艾灸治疗老年尿失禁研究进展) - JIN Wenli (靳文丽); ZHANG Yuanchun (张元春); HAN Jingjing (韩京晶); LIU Jining (刘继宁); FAN Hongxue (范红雪) (中西医结合护理)
Urinary incontinence is a loss of bladder control that’s commonly seen in older adults. It is a common geriatric syndrome which has a serious impact on physical and mental health, quality of life of elderly population. This paper reviewed the clinical studies on moxibustion treatment from the perspective of its concept in Traditional Chinese Medicine, mechanisms and therapeutic methods, highlighted the importance of moxibustion in the treatment of urinary incontinence in the elderly, and provide reference and inspiration for future research on the treatment of urinary incontinence. (尿失禁是老年人中常见疾病, 属于老年综合征之一, 严重影响老年人的身心健康及生活质量。本文从中医对老年人尿失禁的认识、艾灸治疗作用机制、艾灸疗法等进行综述, 分析了艾灸治疗在老年尿失禁中的重要作用, 旨在为后续相关研究工作的开展提供参考。)